Literary Planning and Development in Indonesia Through The Local Literature Community (LLC): A Challenge - Sulaiman Sulaiman; Mintowati Mintowati; Anas Ahmadi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2020)
Planning and fostering literature in Indonesia is very important as an effort to preserve it, especially regional literature and develop its existence. This is important because literature has a noble function, namely voicing the heart and phenomena that occur in society. We see that the development of literature in Indonesia such as